Understanding and Using English Grammar - Azar, Betty Schrampfer (New York : White Plains, 2001)
The book remains a developmental skills text for students of English as a second or foreign language. While focusing on grammar, it promotes the development of all language skills in a variety of ways.
Keywords: English language -- Textbooks for foreign speakers; English language -- Grammar -- Problems, exercises, etc